Role of Artificial Intelligence in Education: Opportunities, Constraints and Policy to Practice Pathwayfor Pakistan (Journal of Asian Development Studies, 2026)
The use of Artificial Intelligence in education is transforming the global educational landscape through the adoption of tutoring, automated evaluation, learning analytics, and generative technologies. The educational impact of AI in Pakistan is limited by structural factors, including disparate connectivity, limited device access, inequitable school infrastructure, teacher capacity issues, and management challenges. The article is a synthesis of evidence from peer-reviewed articles and other key policy and statistical sources to map the current AI-in-education landscape in Pakistan and to suggest a non-theoretical pathway from pilots to scalable reform. Based on the structured literature review and triangulation of secondary data (national education statistics, telecom and internet indicators, and policy documents), we can determine where AI can reasonably providevalue: teacher support, formative assessment, targeted remediation, and administrative efficiency; and not just in higher education and blended-learning settings. Findings indicate a stable trend: perceived learning gains increase with the combination of AI and teacher training, along with a clear assessment policy, and the risk factors center on equity, academic integrity, privacy, and poor institutional preparedness. The paper concludes with policy and implementation recommendations aligned with Pakistan's AI and education reform directions.